Entrepreneurship Education, Digital Literacy, and Digital Entrepreneurial Intention: The Mediating Role of Entrepreneurial Self-Efficacy - Ina Silfina; Jun Surjanti; Meylia Elizabeth Ranu (Journal of Economic Education and Entrepreneurship Studies, 2026)
This study examines the effects of entrepreneurship education and digital literacy on digital entrepreneurial intention, with entrepreneurial self-efficacy positioned as a mediating variable among vocational education students. A quantitative explanatory design was employed, involving 130 students enrolled in digital business and marketing programs. Respondents were selected using proportionate stratified random sampling, and the data were analyzed using Partial Least Squares Structural Equation Modeling. The findings show that entrepreneurship education does not directly influence digital entrepreneurial intention, whereas digital literacy has a significant positive effect. Entrepreneurial self-efficacy also significantly enhances digital entrepreneurial intention and serves as a key psychological mechanism linking entrepreneurship education to students’ intention to pursue digital entrepreneurship. Entrepreneurship education significantly strengthens entrepreneurial self-efficacy, indicating that educational experiences contribute to students’ confidence in identifying and developing digital business opportunities. In contrast, digital literacy does not significantly influence entrepreneurial self-efficacy and has no indirect effect on digital entrepreneurial intention through self-efficacy. These findings demonstrate that digital capability and entrepreneurial confidence operate through different pathways in shaping digital entrepreneurial intention. The study highlights the need for vocational entrepreneurship education to move beyond theoretical instruction by incorporating experiential learning, digital business projects, and confidence-building activities that enable students to translate entrepreneurial knowledge into digital venture intentions.